Identifying barriers to patient advocacy in the promotion of a safety culture: An integrative review - Shoemark, Teena; Foran, Paula (Operating Room Nurses Association of Canada Journal, 2024)
Problem identification: Promoting patient safety, through patient advocacy, is an important part of the perioperative nurse role. However, identified barriers to effective patient advocacy have also reflected deficits in the characteristics of safety culture. This integrative review aims to highlight these barriers and discuss strategies for promoting patient safety within the perioperative context by presenting links between patient advocacy and safety culture. Literature search: An electronic search of the databases, EBSCOhost, Academic search ultimate, Cumulative Index Nursing and Allied Health Literature (CINAHL), Healthsource, MEDLINE and PubMed, was undertaken and yielded ten articles for inclusion. Primary research included in this review consisted of five qualitative studies, three quantitative studies and two case studies. Further literature was used to provide background into this subject and guidance on writing this paper. Data evaluation synthesis: The selected research was critically appraised for methodological quality using JBI critical appraisal checklists for case reports, qualitative and prevalence research. A data extraction table was used to record, group, compare and inform the integrative process of thematic analysis and data synthesis, generating themes that emerged through the selected literature. Implications for practice: Synthesised findings will highlight the importance of patient advocacy by the perioperative nurse to increase patient safety. This review of the literature will present barriers to patient advocacy and discuss the suggestion that the key to greater patient safety may be an organisational commitment to enhance patient advocacy by perioperative nurses allowing them to speak up on behalf of their patients.